Effects of Age, Level of Education and HIV Status on Cognitive Performance in West African Older Adults: The West Africa IeDEA Cohort Collaboration - (:unkn) unknown (My University, 2021)
An in-depth understanding of the impact of aging, cognitive reserve, and HIV status on cognitive function is needed in older West African adults. Ninety-nine HIV-negative and 334 HIV-positive adults aged ≥ 50 years were enrolled in three clinics (Senegal and Côte d'Ivoire) participating in the IeDEA West Africa collaboration. All subjects underwent the Free and Cued Selective Reminding Test (FCSRT) and the Isaacs Set Test (IST). Age (both linear and quadratic), education level, and HIV status effects on Z-scores were assessed using multivariate linear regression models. Interactions between HIV status and age or educational level were tested. In the present cohort of older West African adults, the role of age and educational level on episodic memory and verbal fluency was observed without revealing an interaction between HIV status and age effect. As age had quadratic effects, older HIV-positive adults should not be considered as a unique group irrespective of their age. Low-educated HIV-positive patients had the lowest verbal fluency performance compared to others. Further studies are needed to duplicate these results. In clinical settings, screening and adapted programs focusing on improving cognition in those patients are needed.
Keywords: African Research